Short-term impacts of nitrogen fertilization on a montane grassland ecosystem in a South Asian biodiversity hotspot - Srinivasan, Madhusudan P; Gleeson, Scott K; Arthur, Mary A (Plant ecology & diversity, 2012)
Background: Elevated anthropogenic nitrogen (N) deposition is an important cause of biodiversity decline and disruption of ecosystem function and services, yet these impacts on many globally important ecosystems remain poorly studied. The Western Ghats of India has a N deposition rate that is highest among the 34 world biodiversity hotspots, and is projected to increase to 3.3 g N m⁻² year⁻¹ by 2050.Aims: This study aims to understand N addition effects on the plant community and ecosystem in the montane grasslands of the Nilgiris, Western Ghats.Methods: Plant and soil responses were measured in grassland plots subject to N addition (ambient, 2 and 8 g N m⁻²year⁻¹) and N immobilisation (500 g sucrose N m⁻² year⁻¹) treatments in a region frequently subjected to fire disturbance – the study site was burned 6 months prior to the experiment.Results: Ecosystem responses were consistent with a N-limited system. Soil N availability and leaf tissue N concentration responded positively to N addition. Plant cover and biomass increased with N addition, whereas soil moisture decreased. Unexpectedly, N enrichment had a positive effect on species richness and diversity, although the cover of one important native grass was significantly reduced by the higher N level.Conclusions: These results suggest that there may be a complex interaction of N deposition and the direct and indirect effects of fire in this system, warranting more detailed and longer-term research in this ecosystem.